THE EFFECT OF VARIATIONS IN INITIAL HEATING TEMPERATURE AND MESH SIZE ON THE HARDNESS VALUE AND CALORIFICATION VALUE OF CANDLECRON SHELL BRIQUETTE - Manuel Fortunato D.C.T.; Bernardus Crisanto Putra Mbulu; Danang Murdiyanto (Mechanical, Energy and Material (METAL), 2026)
One of the promising renewable energy sources is biomass, particularly underutilized candlenut shells, which can be processed into briquettes as a superior alternative to charcoal. This study aimed to utilize candlenut shell waste for briquette production, evaluating hardness and calorific value under varying carbonization temperatures (400°C, 500°C, 600°C) and mesh sizes (30 and 100). Briquettes were produced via carbonization and compression. Hardness was measured using a durometer, yielding the highest value of 76.33 HA at 600°C and 100 mesh, and the lowest of 43.58 HA at 400°C and 30 mesh. Calorific value, determined by bomb calorimetry, peaked at 7834.70 cal/g for 500°C and 30 mesh, while the lowest was 5085.24 cal/g at 500°C and 100 mesh. These results demonstrate that optimized carbonization and particle size enhance briquette quality, promoting sustainable biomass utilization for energy applications.